Reinforced collagen with oxidized microcrystalline cellulose shows improved hemostatic effects. (1st June 2017) - Li, Hui; Cheng, Weilu; Liu, Ke; Chen, Lei; Huang, Yudong; Wang, Xiaofeng; Lv, Zhiyong; He, Jinmei; Li, Cheng
Highlights: Collagen/OMCC sponges, denoted M1–M4, were prepared. Addition of 0.25% (w/w) OMCC improved the hemostatic effects of the collagen sponge. M2 can promote increased platelet activation compared with the collagen sponge. M2 could be involved in the intrinsic coagulation pathway to accelerate hemostasis. M2 is not cytotoxic and has satisfactory biodegradability. Abstract: Sponges composed of different levels of composite collagen/oxidized microcrystalline cellulose (collagen/OMCC), denoted M1–M4, were studied to improve the hemostatic effect of single-collagen sponges. Surface morphological observations showed that structural combinations and intermolecular interactions occurred between collagen and OMCC in the composites. M2 presented the best physical properties and platelet activation and was thus selected for the investigations of the in vitro coagulation time and hemostatic and biological effects on animals. The results illustrated that M2 could reduce the length of the activated partial thromboplastin time (APTT) and thrombin time (TT) and presented rapid hemostatic efficiency in the two injury models (P < 0.05). These findings were used to evaluate the hemostatic mechanism of M2, which can promote blood absorption and platelet activation and could be directly involved in the intrinsic coagulation pathway to accelerate hemostasis. Furthermore, M2 was not cytotoxic and was completely biodegraded in subcutaneous tissue within 28 days.